Prediction of stroke reconvalescence after coronary bypass surgery indicated by CT scan parameters. Issue 10 (29th July 2022) - Irqsusi, Marc; Schenk zu Schweinsberg, Titus; Johnson, Felix Allendorff; Dielmann, Kai; Ramzan, Rabia; Vogt, Sebastian; Mirow, Nikolas; Rastan, Ardawan J.
Abstract: Background: Stroke in the postoperative time course after heart surgery remains a serious risk. Cranial computer tomography (CCT) is the first line option to detect severe intracranial damage. However, only few data are available to predict neurological outcome. Using visual rating scales (VRSs), this study addresses reliability and effectivity to indicate neurological status and likelyhood of improvement. Methods: In a single‐center retrospective evaluation, 3719 patients underwent coronary bypass surgery. Because of a delayed recovery phase and neurologic deficits after cardiac surgery 109 patients had a cranial CT scan in the early postoperative period. The incidence of clinically relevant findings within the imaging was rated by an experienced neuroradiologist using two VRS, that is, the age‐related white matter changes (ARWMCs) and the Mendes–Ribeiro visual rating scale (MRVRS). Both are computer‐assisted measurement schemes to detect stroke‐related intracranial damage. Follow‐up was investigated with regard to clinical outcome and patient‐related risk profiles. Results: Of 109 patients with postoperative cranial CT scans due to prolonged recovery phases or proven neurological damage 44.5% had one cerebral defect in CCT imaging scans only. The others showed multiple defects. During hospital stay, 92.3% experienced neurological improvement exposing reduced ARWMC, while 7.1% had no improvement and correlating high scores. Of both scales, the ARWMC‐VRS demonstrated superior accuracy and discrimination. The preoperative ejection fraction (EF), arteriosclerotic degeneration of carotid arteries, and reduced glomerular filtration rate were found to have a high correlation ( r = 0.0005) with the latter group. In‐hospital mortality of this cohort was 8.18%. Conclusion: Both the ARWMC and MRVRS were found to be appropriate. They reliably discriminate the groups of stroke patients after coronary artery bypass grafting (CABG) in the analysis of CCT images. When applied at the onset of neurological symptoms both scales are able to predict neurological reconvalescence upon hospital dismission. The ARWMC scale appeared superior as it demonstrated better accuracy and discrimination. The use of both VRS in patients with suspected stroke after CABG surgery can give insightful information toward a progression of neurological dysfunction or postoperative improvement.